Agências reguladoras independentes?: especialização e captura nas trajetórias de carreira dos reguladores federais brasileiros - Vieira, Alexandre Sérgio Alves (2015)
This study analyzes profiles and career paths of directors and counselors from the following federal agencies: ANEEL, ANATEL, ANP, ANVISA, ANS, ANA, ANCINE, ANTAQ, ANTT e ANAC. We observe dimensions relating with conditions which, in theory, allow more decision-making autonomy to Brazilian federal regulators: 1) regulator’s level of expertise and skilled knowledge, watching his trainig area, level of education and previous experience in the regulated sector; 2) the existence of party affiliation before his appointment to the post at the agency; 3) the existence of cases of renewal regulators, beyond the government mandates of different presidents; 4) the professional origin of regulators and destination after their performance in regulatory agencies. At the same time, it is observed the institutional design of these Brazilian agencies and how some aspects of its structure and process can interfere with the outcome of the regulatory process, specially in regard to how regulators are indicated. Among the main results of this work, we highlight the strong connection between the training area of regulators and the playing field of regulatory agencies; the recovery of post-graduate courses in qualifying a candidate for a federal regulatory agency; and the proof of previous professional experience in the regulated sector, indicating that Brazilian regulators have relevant indicators of specialization and expertise in the sector. There have also been cases of indicated and reappointed regulators by different presidents, reinforcing the hypothesis that value expertise. Regarding political capture, stands out that just under a third of tregulators had previous party affiliation before their appointments. Most regulators are selected within the public service, but most of them will work in the private industry sphere, reinforcing the evidence that there may have been capture during their mandates in the agency. It is clear, also, a trend of strengthening of agencies’ bureaucracy from the end of the first term of President Lula, movement wich has increased in President Dilma Rousseff’s first term.